On the effects of high temperature and high pressure on the hydrogen solubility in rhenium - Scheler, Thomas; Degtyareva, Olga; Gregoryanz, Eugene (The Journal of chemical physics, 2011)
In situ x-ray diffraction experiments on rhenium hydride compressed up to 46 GPa reveal a hydrogen solubility ( x ) significantly larger than the previously assumed saturation limit of x ∼ 0.38(4). In the layered anti-CdI 2 -type structure of rhenium hydride, the hydrogen solubility was found to increase to x ∼ 0.5 at 15 GPa over time. When heated to temperatures above 420 K at pressures above 23 GPa, rhenium hydride undergoes an isomorphous phase transition into the NiAs-type structure accompanied by an increase in hydrogen solubility to x ∼ 0.85. The formation of fully stoichiometric rhenium hydride is discussed.